KARAKTERISTIK BIOLOGI KUDA LAUT (Hippocampus spp) SEBAGAI PENGETAHUAN DASAR BUDIDAYANYA - Dwi Eny Djoko Setyono (Pusat Penelitian Oseanografi LIPI, 2020)
Many species of marine organisms live in Indonesian waters have a potential for aquaculture (fishes, crustaceans, mollusc, echinoderm, and algae). They are cultured for food resources, the basis for cosmetic and natural medicine, and also as ornamental fish for marine aquarium. Seahorse (Syngnathidae: Hippocampus) is a marine fish which has high ecological and economic value. Fishing pressure of wild seahorse increased significantly when buyers offering an attractive price for the catch. High levels of fishing effort keep the wild stocks of seahorses well below the level that could be supported by natural growth and recruitment. Aquaculture for seahorses is very important to support sustainable production and to maintain the wild population in steady condition. Culture technique for seahorses has been developed in some countries, including Indonesia. However, seahorse aquaculture in Indonesia has not been achieved as expected due to the limited understanding of some biological characteristics. This manuscript deliberates some biological characteristics that useful as basic knowledge for seahorse aquaculture.